Thermally conductive filler, method for producing thermally conductive filler, and thermally conductive resin composition

By using specific proportions of large-diameter electromelted alumina particles, medium-diameter inorganic particles and small-diameter inorganic particles in thermal conductivity resins, the problem of high hardness of thermal conductivity resins in the prior art is solved, and excellent thermal conductivity and low hardness are achieved The resin composition is suitable for the heat dissipation needs of electrical components such as lithium-ion batteries.

CN119137237APending Publication Date: 2024-12-13MITSUBISHI MATERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380030733.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The conventional thermally conductive resin compositions are difficult to keep the resin hardness low when improving thermal conductivity, and the materials used are not easily filled highly, making it difficult to meet the heat dissipation needs of high-current electrical components such as lithium-ion batteries.

Method used

The combination of coarse inorganic particles and small-diameter inorganic particles is adopted, specifically the mixture of large-diameter electromelting alumina particles, medium-diameter inorganic particles and small-diameter inorganic particles, the particle ratio is 60:40-100:0, and the content of small-diameter inorganic particles is 15. With a combination of more than % and less than 30 mass%, the thermal conductivity is improved and the hardness of the resin is maintained.

Benefits of technology

The thermal conductivity resin composition with excellent thermal conductivity and low hardness is realized, and is suitable for heat dissipation parts such as lithium-ion batteries that output high current electrical components, and has a low cost and a thermal conductivity of up to 30W/mK or more.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137237A_ABST
    Figure CN119137237A_ABST
Patent Text Reader

Abstract

A thermally conductive filler containing coarse inorganic particles and small-diameter inorganic particles, the coarse inorganic particles including large-diameter fused alumina particles having an average particle diameter in the range of 20 [mu] m to 50 [mu] m inclusive and medium-diameter inorganic particles having an average particle diameter in the range of 1.0 [mu] m to 10 [mu] m inclusive at a mass ratio of 60: 40 to 100: 0, the average particle diameter of the small-diameter inorganic particles is within the range of 0.1 [mu] m or more and less than 1.0 [mu] m, and the content of the small-diameter inorganic particles is within the range of 15% by mass or more and 30% by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive filler, a method for producing the thermally conductive filler and a thermally conductive resin composition.

[0002] This application claims priority based on patent application No. 2022-056539 applied for in Japan on March 30, 2022, and its content is cited here. Background Art

[0003] In recent years, with the development of electric vehicles, fuel cell vehicles, etc., the current of electrical components has been continuously increased, and the heat generated by electrical components has also increased. For example, lithium-ion batteries for automobiles generate more heat due to the long-term continuous output of large current electricity, and the large amount of heat generated needs to be effectively dissipated to the outside. Therefore, as a heat dissipation component in the part that requires insulation of electrical components such as lithium-ion batteries that output large currents, a thermally conductive resin composition with excellent thermal conductivity is sometimes used.

[0004] Conventionally, thermally conductive resin compositions include those in which a thermally conductive filler having excellent thermal conductivity is dispersed in a resin material having excellent insulation and moldability. As thermally conductive fillers, fused alumina (Al 2 O 3 ) or inorganic materials such as silicon carbide (SiC) (Patent Document 1). Patent Document 1 describes α-alumina (fused alumina) with an average particle size greater than 10 μm and less than 60 μm and silicon carbide with an average particle size of less than 10 μm as thermally conductive fillers. In addition, as a thermally conductive filler, it is being considered to mix and use thermally conductive fillers with two sizes of average particle sizes (Patent Document 2). Patent Document 2 describes the following: As thermally conductive fillers with two sizes of average particle sizes, silicon carbide with an average particle size of 50 to 100 μm and silicon carbide with an average particle size of less than 10 μm are mixed in a weight ratio of 1:1 to 3:1.

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 7-304946 (A)

[0006] Patent Document 2: Japanese Patent Application Publication No. 2004-6981 (A)

[0007] The thermally conductive filler used in the thermally conductive resin composition is preferably a material that is easily available industrially, has excellent thermal conductivity, has high filling properties in the resin, and does not easily increase the hardness of the resin excessively even if added to the resin. Although the fused alumina described in Patent Document 1 is an industrially easily available material, there is a limit to improving the thermal conductivity by fused alumina alone. In addition, silicon carbide described in Patent Document 2 has high thermal conductivity compared to fused alumina, but it is difficult to fill a high degree of the resin. Summary of the invention

[0008] The present invention has been completed in consideration of such a situation, and its object is to provide a thermally conductive filler and a method for producing the same, and a thermally conductive resin composition having excellent thermal conductivity and low hardness. The thermally conductive filler uses a material that is easily available industrially, has excellent thermal conductivity, has high filling properties for resin, and is unlikely to excessively increase the hardness of the resin even when added to the resin.

[0009] In order to solve the above-mentioned problems, the thermally conductive filler of the present invention is composed as follows: it contains coarse inorganic particles and small-diameter inorganic particles, the coarse inorganic particles contain large-diameter fused alumina particles with an average particle size in the range of 20 μm to 50 μm and medium-diameter inorganic particles with an average particle size in the range of 1.0 μm to 10 μm in a mass ratio of 60:40 to 100:0, the average particle size of the small-diameter inorganic particles is in the range of 0.1 μm to less than 1.0 μm, and the content of the small-diameter inorganic particles is in the range of 15 mass % to 30 mass %.

[0010] According to the thermally conductive filler of the present invention constituted as above, since fine small-diameter inorganic particles having an average particle size in the range of 0.1 μm or more and less than 1.0 μm exist in the gaps between the coarse inorganic particles, the thermal conductivity becomes high. In addition, according to the thermally conductive filler of the present invention, since the content of large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles is within the above-mentioned range, when added to the resin, it is not easy to excessively increase the hardness of the resin. In addition, the large-diameter fused alumina particles used in the thermally conductive filler of the present invention are easily obtained industrially. Therefore, by using the thermally conductive filler of the present invention, a thermally conductive resin composition having excellent thermal conductivity and low hardness can be obtained at low cost.

[0011] Here, the thermally conductive filler of the present invention may have a thermal conductivity of 30 W / mK or more at 20°C.

[0012] In this case, a thermally conductive resin composition having excellent thermal conductivity can be obtained more reliably.

[0013] The thermally conductive filler of the present invention may have a hardness of 65 or less as measured by an Asker C hardness meter when 1100 parts by mass of the thermally conductive filler is added to 100 parts by mass of the silicone resin.

[0014] In this case, since the hardness of the resin when added to the silicone resin is the above-mentioned value, it can be added to various resins other than the silicone resin without excessively increasing the hardness.

[0015] The manufacturing method of the thermally conductive filler of the present invention is as follows: the manufacturing method is the manufacturing method of the thermally conductive filler of the present invention described above, wherein large-diameter fused alumina particles having an average particle size in the range of 20 μm to 50 μm, medium-diameter inorganic particles having an average particle size in the range of 1.0 μm to 10 μm, and small-diameter inorganic particles having an average particle size in the range of 0.1 μm to less than 1.0 μm are mixed, so that the mass ratio of the large-diameter fused alumina particles to the medium-diameter inorganic particles is 60:40 to 100:0 and the content of the small-diameter inorganic particles is in the range of 15 mass % to 30 mass %.

[0016] According to the method for producing a thermally conductive filler of the present invention configured as above, since large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles are mixed in the above-mentioned ratio, the thermally conductive filler of the present invention can be produced industrially advantageously.

[0017] The thermally conductive resin composition of the present invention comprises a resin and the thermally conductive filler of the present invention.

[0018] The thermally conductive resin composition of the present invention having the above-described structure contains the thermally conductive filler of the present invention, and therefore has excellent thermal conductivity and low hardness.

[0019] Here, the thermally conductive resin composition of the present invention may have a thermal conductivity of 3.25 W / mK or more at 40°C.

[0020] In this case, the thermally conductive resin composition has high thermal conductivity at 40° C. and can therefore be advantageously used as a heat dissipation member for electrical components that output a large current, such as lithium ion batteries.

[0021] According to the present invention, a thermally conductive filler and a method for producing the same, as well as a thermally conductive resin composition having excellent thermal conductivity and low hardness can be provided. The thermally conductive filler comprises fused alumina particles that are easily available industrially, has excellent thermal conductivity, has high filling properties for resin, and is unlikely to excessively increase the hardness of the resin even when added to the resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the particle size distribution of the large diameter fused alumina particles used in the examples.

[0023] Figure 2 is the particle size distribution of the medium diameter inorganic particles used in the examples.

[0024] Figure 3 This is the particle size distribution of the small-diameter inorganic particles used in the examples.

[0025] Figure 4It is an estimated value of the particle size distribution of the mixed powder prepared in Example 1 of the present invention.

[0026] Figure 5 It is a triangular diagram showing the composition of the mixed powder prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0027] Hereinafter, a thermally conductive filler, a method for producing a thermally conductive filler, and a thermally conductive resin composition according to an embodiment of the present invention will be described. In addition, the embodiments shown below are specific descriptions for better understanding of the gist of the invention, and do not limit the present invention unless otherwise specified.

[0028] (Thermal conductive filler)

[0029] The thermally conductive filler includes coarse inorganic particles and small-diameter inorganic particles. The coarse inorganic particles include large-diameter fused alumina particles with an average particle size in the range of 20 μm or more and 50 μm or less and medium-diameter inorganic particles with an average particle size in the range of 1.0 μm or more and 10 μm or less in a mass ratio of 60:40 to 100:0. The average particle size of the small-diameter inorganic particles is in the range of 0.1 μm or more and less than 1.0 μm. The average particle size of the large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles is a value measured using a laser diffraction scattering particle size distribution measuring device (MT3300EXII: Microtrac Bell Co., Ltd.). The content of small-diameter inorganic particles is in the range of 15% by mass or more and 30% by mass or less.

[0030] Fused alumina particles are particles obtained by pulverizing a lump (fused alumina) melted and recrystallized in an electric furnace, and are polygonal particles having an average sphericity of about 0.7 or less (e.g., 0.2 to 0.8 or 0.3 to 0.8). The average sphericity can be obtained by analyzing the target powder using FijiimageJ, for example.

[0031] The content of the coarse inorganic particles in the thermally conductive filler may be 70% by mass or more and 85% by mass or less, 71% by mass or more and 80% by mass or less, or 72% by mass or more and 75% by mass or less.

[0032] The thermally conductive filler may be composed of coarse inorganic particles and small-diameter inorganic particles.

[0033] The particle shape of the large-diameter fused alumina particles is not particularly limited, and may be, for example, spherical, cubic, or irregular. The large-diameter fused alumina particles may be crushed products that are easily available industrially. The average particle size of the large-diameter fused alumina particles is preferably in the range of 25 μm to 45 μm, and more preferably in the range of 30 μm to 40 μm.

[0034] The particle shape of the medium diameter inorganic particles is not particularly limited, and may be, for example, spherical, cubic, or irregular. The medium diameter inorganic particles are preferably made of a material having a thermal conductivity of 30 W / mK or more at 20°C.

[0035] As the material of the medium diameter inorganic particles, for example, silicon carbide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, magnesium oxide, and zinc oxide can be used. The average particle size of the medium diameter inorganic particles is preferably in the range of 2 μm to 6 μm, more preferably in the range of 3 μm to 5 μm.

[0036] The particle shape of the small-diameter inorganic particles is not particularly limited, and may be, for example, spherical, cubic, or irregular. The small-diameter inorganic particles are preferably made of a material having a thermal conductivity of 30 W / mK or more at 20°C.

[0037] As the material of the small-diameter inorganic particles, for example, silicon carbide, aluminum oxide, aluminum nitride, boron nitride, silicon nitride, magnesium oxide, and zinc oxide can be used. The average particle size of the small-diameter inorganic particles is preferably in the range of 0.20 μm to 0.80 μm, more preferably in the range of 0.30 μm to 0.70 μm.

[0038] In the thermally conductive filler of the present embodiment, the ratio of the average particle size of the medium-diameter inorganic particles to the average particle size of the large-diameter fused alumina particles is preferably 8 / 10 or less, more preferably 5 / 10 or less, and particularly preferably 3 / 10 or less. Furthermore, the ratio of the average particle size of the medium-diameter inorganic particles to the average particle size of the large-diameter fused alumina particles is preferably 1 / 20 or more. Furthermore, the ratio of the average particle size of the small-diameter inorganic particles to the average particle size of the large-diameter fused alumina particles is preferably 9 / 100 or less, more preferably 6 / 100 or less, and particularly preferably 4 / 100 or less. Furthermore, the ratio of the average particle size of the small-diameter inorganic particles to the average particle size of the large-diameter fused alumina particles is preferably 1 / 200 or more.

[0039] In the thermally conductive filler of the present embodiment, the conductivity is improved by the presence of small-diameter inorganic particles in the gaps between the coarse inorganic particles (between the large-diameter fused alumina particles, between the large-diameter fused alumina particles and the medium-diameter inorganic particles, and between the medium-diameter inorganic particles). In order to make it easier for the small-diameter inorganic particles to exist in the gaps between the coarse inorganic particles, the content ratio of the large-diameter fused alumina particles to the medium-diameter inorganic particles is set to a ratio of 60:40 to 100:0 in terms of mass ratio in the present embodiment.

[0040] The content ratio (mass ratio) of large-diameter fused alumina particles to medium-diameter inorganic particles is preferably 80:20 to 100:0, more preferably 80:20 to 90:10. In addition, when the content of small-diameter inorganic particles is too small, the small-diameter inorganic particles present between the particles of the coarse inorganic particles will become less and the effect of improving the conductivity will become lower. When the content of small-diameter inorganic particles is too much, there will be small-diameter inorganic particles dispersed in the resin of the thermally conductive resin composition, which may excessively increase the hardness of the thermally conductive resin composition. Therefore, in this embodiment, the content of small-diameter inorganic particles relative to the thermally conductive filler as a whole is set to be within the range of 15% by mass or more and 30% by mass or less. The content of small-diameter inorganic particles is preferably within the range of 20% by mass or more and 30% by mass or less. In addition, in the thermally conductive filler of the present embodiment, it is preferred that the particle size distribution of the thermally conductive filler as a whole has more than two peaks. It is preferably a bimodal property with two peaks, and more preferably a trimodal property with three peaks. When the particle size distribution is bimodal or more, particles having different particle sizes can easily enter the gaps, and the filling amount can be further increased.

[0041] In the thermally conductive filler of this embodiment, the thermal conductivity of the thermally conductive filler as a whole is preferably 30 W / mK or more. The thermal conductivity of each of the large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles constituting the thermally conductive filler is preferably 30 W / mK or more.

[0042] The thermally conductive filler of the present embodiment is preferably added in an amount of 600 parts by mass or more and 1500 parts by mass or less, and more preferably in an amount of 800 parts by mass or more and 1300 parts by mass or less, relative to 100 parts by mass of the resin. When the amount of the thermally conductive filler of the present embodiment is within the above range, the thermal conductivity can be improved without excessively increasing the hardness of the thermally conductive resin composition. The thermally conductive filler of the present embodiment preferably has a hardness of 65 or less measured by an Asker C hardness meter when 1100 parts by mass of the thermally conductive filler of the present embodiment is added to 100 parts by mass of the silicone resin.

[0043] According to the thermally conductive filler of the present embodiment constructed as above, since fine small-diameter inorganic particles with an average particle size of 0.1 μm or more and less than 1.0 μm exist in the gaps between the coarse inorganic particles, the thermal conductivity is high. In addition, according to the thermally conductive filler of the present embodiment, since the content of large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles is within the above-mentioned range, when added to the resin, it is not easy to make the hardness of the resin excessively high. In addition, the large-diameter fused alumina particles used in the thermally conductive filler of the present embodiment are easily obtained industrially. Therefore, by using the thermally conductive filler of the present embodiment, a thermally conductive resin composition with excellent thermal conductivity and low hardness can be obtained at low cost.

[0044] When the thermal conductivity of the thermally conductive filler of the present embodiment at 20° C. is 30 W / mK or more, a thermally conductive resin composition having excellent thermal conductivity can be obtained more reliably.

[0045] The thermal conductivity of the thermally conductive filler at 20° C. may be 35 W / mK or more, or 40 W / mK or more. The thermal conductivity may be 250 W / mK or less.

[0046] Furthermore, when the thermally conductive filler of the present embodiment has a hardness of 65 or less as measured by an Asker C hardness meter when 1100 parts by mass of the thermally conductive filler of the present embodiment is added to 100 parts by mass of silicone resin, the thermally conductive filler can be added to various resins other than silicone resin without excessively increasing the hardness.

[0047] The hardness may be 60 or less, or 55 or less.

[0048] The hardness may be 0 or more.

[0049] (Method for producing thermally conductive filler)

[0050] In the method for manufacturing a thermally conductive filler of the present embodiment, large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles are mixed. The mixing order of large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles is not limited. For example, large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles can be mixed at the same time, or a mixture of large-diameter fused alumina particles and medium-diameter inorganic particles can be mixed with small-diameter inorganic particles, or a mixture of medium-diameter inorganic particles and small-diameter inorganic particles can be mixed with large-diameter fused alumina particles, or a mixture of large-diameter fused alumina particles and small-diameter inorganic particles can be mixed with medium-diameter inorganic particles. Furthermore, mixing can be performed in a dry manner or in a wet manner.

[0051] The mixing ratio of the large-diameter fused alumina particles and the medium-diameter inorganic particles is such that the mass ratio of the large-diameter fused alumina particles to the medium-diameter inorganic particles is 60:40 to 100:0, preferably 80:20 to 100:0, and more preferably 80:20 to 90:10. The mixing ratio of the small-diameter inorganic particles is such that the content of the small-diameter inorganic particles relative to the total amount of the large-diameter fused alumina particles, the medium-diameter inorganic particles, and the small-diameter inorganic particles is within a range of 15% by mass or more and 30% by mass or less, and preferably 20% by mass or more and 30% by mass or less.

[0052] According to the method for producing a thermally conductive filler of the present embodiment configured as above, since large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles are mixed in the above-mentioned ratio, the thermally conductive filler of the present embodiment can be produced industrially advantageously.

[0053] (Thermal conductive resin composition)

[0054] The thermally conductive resin composition of the present embodiment contains a resin and the thermally conductive filler of the present embodiment.

[0055] The thermally conductive resin composition may contain, for example, 600 parts by mass or more and 1500 parts by mass or less of the thermally conductive filler per 100 parts by mass of the resin. The thermal conductivity at 40° C. is preferably 3.25 W / mK or more, more preferably 3.40 W / mK or more.

[0056] The resin contained in the thermally conductive resin composition is not particularly limited, and known resins can be used. The resin can be a thermoplastic resin or a thermosetting resin. Examples of resins include hydrocarbon resins, unsaturated polyester resins, acrylic resins, vinyl ester resins, epoxy resins, xylene formaldehyde resins, guanamine resins, diallyl phthalate resins, phenolic resins, furan resins, polyimide resins, melamine resins, urea resins, silicone resins, etc. In addition, in the present embodiment, the resin includes rubber.

[0057] Since the thermally conductive resin composition of the present embodiment configured as above contains the thermally conductive filler of the present embodiment, it has excellent thermal conductivity and low hardness. Therefore, it can be used as a heat dissipation component of various parts. In particular, a thermally conductive resin composition having a thermal conductivity of 3.25 W / mK or more at 40° C. can be advantageously used as a heat dissipation component of electrical components that output a large current, such as lithium ion batteries.

[0058] Although an embodiment of the present invention has been described above, this embodiment is only illustrative and does not limit the scope of the invention. This embodiment can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the main purpose of the invention. This embodiment or its modification is included in the scope or main purpose of the invention, and is also included in the invention described in the scope of the claims and its equivalent.

[0059] Example

[0060] Hereinafter, the results of a confirmation experiment conducted to confirm the effectiveness of the present invention will be described.

[0061] The large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles used in this example are as follows: The particle size distribution was measured using a laser diffraction scattering type particle size distribution measuring device (MT3300EXII: Microtrac Bell Co., Ltd.).

[0062] (1) Large diameter fused alumina particles

[0063] Alumina particles having an average particle size of 33.3 μm and a thermal conductivity of 30 W / mK or more at 20°C. Figure 1 The particle size distribution is shown in .

[0064] (2) Medium diameter inorganic particles

[0065] Low Soda Alumina particles with an average particle size of 3.9 μm and a thermal conductivity of 30 W / mK or more at 20°C. Figure 2 The particle size distribution is shown in .

[0066] (3) Small diameter inorganic particles

[0067] Low soda alumina particles with an average particle size of 0.49 μm and a thermal conductivity of 30 W / mK or more at 20°C. Figure 3 The particle size distribution is shown in .

[0068] [Experimental Example 1]

[0069] The particles were weighed and put into a mortar so that the content ratio (mass ratio) of large-diameter fused alumina particles and medium-diameter inorganic particles and the content of small-diameter inorganic particles became the values ​​shown in Table 1 below, and mixed using a grinding rod to prepare a mixed powder.

[0070] 0.5 g of silicone rubber (KE-1051J A, manufactured by Shin-Etsu Chemical Co., Ltd.) was placed in a container, and the mixed powder was added in portions of 0.5 g each time, and kneaded at 2000 rpm for 2 minutes using a centrifugal deaerator. The obtained mixture was touched with fingers, and the amount of mixed powder added when it became brittle and could not be molded was taken as the limit filling amount. The results are shown in Table 1 below.

[0071] [Table 1]

[0072]

[0073] From the results in Table 1, it is confirmed that the maximum filling amount of the mixture in which the blending amount (mass ratio) of large-diameter fused alumina particles and medium-diameter inorganic particles is in the ratio of 60:40 to 100:0 and the content of small-diameter inorganic particles is in the range of more than 15 mass % and less than 30 mass % is more than 1,300 parts by mass, and the filling amount for silicone rubber is high.

[0074] [Example 1 of the present invention]

[0075] The large-diameter fused alumina particles were 68% by mass, the medium-diameter inorganic particles were 17% by mass, and the small-diameter inorganic particles were 15% by mass, and mixed using a grinding rod and a mortar to prepare a mixed powder. The content ratio of the large-diameter fused alumina particles to the medium-diameter inorganic particles in the obtained mixed powder was 80:20.

[0076] A total of 22 g of mixed powder was added to the rubber mixture by repeating the following operation: to a rubber mixture containing 1 g of silicone rubber (KE-1051J A) and 1 g of silicone rubber (KE-1051J B), the mixed powder was added in a manner of several grams each time, and kneaded at 2000 rpm for 2 minutes using a centrifugal degassing machine. The rubber mixture to which the mixed powder was added was left to stand at room temperature (25° C.) for 24 hours to cure, thereby obtaining a resin composition.

[0077] The estimated value of the particle size distribution of the mixed powder obtained in Example 1 of the present invention was calculated from the particle size distribution of the large-diameter fused alumina particles, the medium-diameter inorganic particles, and the small-diameter inorganic particles and their blending amounts. The results are shown in Figure 4 middle.

[0078] Depend on Figure 4 It is found that the mixed powder obtained in Inventive Example 1 has three peaks at 33.3 μm, 3.9 μm, and 0.49 μm.

[0079] [Examples 2 to 6 of the present invention, comparative examples 1 to 3]

[0080] A resin composition was obtained in the same manner as in Inventive Example 1 except that the ratios of the large-diameter fused alumina particles, the medium-diameter inorganic particles, and the small-diameter inorganic particles in the mixed powder were as shown in Table 2 below.

[0081] Table 1 shows the content ratio (mass ratio) of the large-diameter fused alumina particles and the medium-diameter inorganic particles in the mixed powders prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3.

[0082] exist Figure 5 : A triangular diagram showing the composition of the mixed powders prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 is shown in FIG.

[0083] [evaluate]

[0084] The thermal conductivity and hardness of the resin compositions obtained in Inventive Examples 1 to 6 and Comparative Examples 1 to 3 were measured by the following methods.

[0085] (Thermal conductivity)

[0086] The cured resin composition was molded into 28 mm × 28 mm × 3 mm and 28 mm × 28 mm × 5 mm, and measured using a thermal conductivity measuring device (IE-1237, manufactured by IWATSU ELECTRIC CO., LTD.). As the measurement conditions, the high temperature side of the device was set to 80°C, the low temperature side was set to 15°C, and the measurement was performed under the condition that the sample temperature was about 40°C. The average value of the thermal conductivity of the resin composition of 3 mm and the thermal conductivity of the resin composition of 5 mm thickness was taken as the thermal conductivity of the resin composition at 40°C.

[0087] (hardness)

[0088] Since the resin composition of the present invention can be deformed even after curing, the resin composition was molded into a thickness of 7 mm using a hand press to prepare a sample for hardness measurement. The hardness of the obtained sample was measured using an Asker C hardness tester.

[0089] [Table 2]

[0090]

[0091] From the results in Table 2, it can be seen that the thermal conductivity of the resin composition obtained in Examples 1 to 6 of the present invention using mixed powders in which the contents of large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles are within the range of the present invention is high, being 3.25 W / mK or more, and the hardness measured by an Asker C hardness meter is low, being 65 or less. The reason why the thermal conductivity of the resin composition obtained in Examples 1 to 6 of the present invention shows a high value is that the thermal conductivity of the resin composition becomes high due to the presence of small-diameter inorganic particles between the coarse inorganic particles (large-diameter fused alumina particles, medium-diameter inorganic particles). In addition, the reason why the hardness of the resin composition obtained in Examples 1 to 6 of the present invention is relatively low is that the small-diameter inorganic particles are present between the coarse inorganic particles and the amount of small-diameter inorganic particles dispersed in the resin is relatively small.

[0092] In contrast, the resin compositions obtained in Comparative Examples 1 to 3 used the same large-diameter fused alumina particles, medium-diameter inorganic particles, and small-diameter inorganic particles as in Examples 1 to 6 of the present invention, but the thermal conductivity of the resin compositions was lower than 3.25 W / mK, and the hardness measured by the Asker C hardness meter exceeded 65. In particular, in Comparative Example 1, the hardness of the resin composition was significantly higher, 80. It is believed that the thermal conductivity is lowered because the proportion of small-diameter inorganic particles in the resin composition of Comparative Example 1 is higher than the range of the present invention, and the amount of large-diameter fused alumina particles or medium-diameter inorganic particles is relatively reduced. In addition, it is believed that the hardness is higher in the resin composition of Comparative Example 1 because the amount of small-diameter inorganic particles dispersed in the resin is increased. In addition, it is believed that the thermal conductivity is lowered in the resin composition of Comparative Example 2 because the proportion of small-diameter inorganic particles is lower than the range of the present invention, and the amount of large-diameter fused alumina particles or medium-diameter inorganic particles is relatively increased, and there are more voids without small-diameter inorganic particles. In addition, it is considered that the ratio of large-diameter fused alumina particles to medium-diameter inorganic particles in the resin composition of Comparative Example 3 is less than the range of the present invention, so the thermal conductivity is low. In addition, it is considered that the ratio of medium-diameter inorganic particles and small-diameter inorganic particles to large-diameter fused alumina particles in the resin composition of Comparative Example 3 is large, and the specific surface area of ​​the thermally conductive filler as a whole is large, so the hardness of the resin composition is high, which is 75.

[0093] Industrial Applicability

[0094] Provided are a thermally conductive filler, a method for producing the same, and a thermally conductive resin composition having excellent thermal conductivity and low hardness. The thermally conductive filler comprises fused alumina particles that are easily available industrially, has excellent thermal conductivity, has high filling properties for resin, and is unlikely to excessively increase the hardness of the resin even when added to the resin.

Claims

1. A thermally conductive filler comprising coarse inorganic particles and small-diameter inorganic particles, The coarse inorganic particles include large-diameter fused alumina particles having an average particle size in the range of 20 μm to 50 μm and medium-diameter inorganic particles having an average particle size in the range of 1.0 μm to 10 μm at a mass ratio of 60:40 to 100:

0. The average particle size of the small-diameter inorganic particles is in the range of 0.1 μm or more and less than 1.0 μm. The content of the small-diameter inorganic particles is within a range of 15 mass % or more and 30 mass % or less.

2. The thermally conductive filler according to claim 1, wherein The thermal conductivity of the thermally conductive filler at 20° C. is greater than 30 W / mK.

3. The thermally conductive filler according to claim 1 or 2, wherein: When 1100 parts by mass of the thermally conductive filler is added to 100 parts by mass of the silicone resin, the hardness measured by an Asker C hardness meter is 65 or less.

4. A method for producing a thermally conductive filler, wherein: The manufacturing method is a manufacturing method of the thermally conductive filler according to any one of claims 1 to 3, Large-diameter fused alumina particles with an average particle size in the range of 20 μm to 50 μm, medium-diameter inorganic particles with an average particle size in the range of 1.0 μm to 10 μm, and small-diameter inorganic particles with an average particle size in the range of 0.1 μm to less than 1.0 μm are mixed so that the mass ratio of the large-diameter fused alumina particles to the medium-diameter inorganic particles is 60:40 to 100:0 and the content of the small-diameter inorganic particles is in the range of 15 mass % to 30 mass %. 5 . A thermally conductive resin composition comprising a resin and the thermally conductive filler according to claim 1 .

6. The thermally conductive resin composition according to claim 5, wherein The thermal conductivity of the thermally conductive resin composition at 40° C. is 3.25 W / mK or more.